2022
DOI: 10.3389/fneur.2022.921173
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of COVID-19 and the Pandemic on Tinnitus Patients

Abstract: This study aimed to explore the effect of COVID-19 and the pandemic period on the tinnitus-related complaints of patients with chronic tinnitus. Ninety-six patients who were diagnosed with chronic tinnitus before the pandemic were enrolled in this study. Before the pandemic and in January 2022, all patients used the Visual Analog Scale (VAS) to assess tinnitus loudness, annoyance, and effect on everyday life, sleep, and concentration. Additionally, patients filled the Tinnitus Handicap Inventory (THI) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…44% of 25 participants diagnosed with COVID-19 described an increase in tinnitus loudness after diagnosis. In studies in the literature, it has been reported that tinnitus exacerbates after COVID-19 infection in 24.3% to 40% of people with tinnitus (2,12,20). These results can be considered compatible with the findings of our study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…44% of 25 participants diagnosed with COVID-19 described an increase in tinnitus loudness after diagnosis. In studies in the literature, it has been reported that tinnitus exacerbates after COVID-19 infection in 24.3% to 40% of people with tinnitus (2,12,20). These results can be considered compatible with the findings of our study.…”
Section: Resultssupporting
confidence: 93%
“…Tinnitus was found to be associated with emotional distress, depressive symptoms, anxiety, and insomnia (8). There are few research investigating how the COVID-19 epidemic has affected people's subjective perceptions of tinnitus (2,3,(9)(10)(11)(12). In studies, changes in lifestyle such as social isolation, emotional states, insomnia, financial concerns during the pandemic period exacerbated the tinnitus complaint of people and caused these issues to be perceived as more disturbing.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent investigations present slightly more divergent findings. One study demonstrated a notable increase in tinnitus loudness, reduced ability to concentrate because of tinnitus, and higher THI scores, but only in patients who contracted COVID-19 [45]. Intriguingly, this study also observed a significant rise in hyperacusis among uninfected tinnitus patients.…”
Section: Discussionmentioning
confidence: 45%
“…COVID-19 infection may present with otological manifestations such as hearing loss, tinnitus, vertigo, ear fullness, and earache [ 18 ]. Even if some patients experienced ear symptoms, these were mostly transitory, although some studies have shown evidence for the worsening of preexisting tinnitus as a possible long-term effect of COVID-19 [ 21 , 22 ]. In our practice, we administer questionnaires to patients to assess how troublesome the tinnitus is for them, as well as how it affects their daily activity and ability to function.…”
Section: Discussionmentioning
confidence: 99%